A new colorimetric method for determination of formaldehyde in sea food based on anti-aggregation of gold nanoparticles - Mathaweesansurn, Arjnarong; Detsri, Ekarat (My University, 2022)
A new colorimetric method based on anti-aggregation of gold nanoparticles (AuNPs) in the presence of melamine for sensitive and selective determination of formaldehyde was developed. The citrate capped AuNPs was synthesized by Turkevich method. A certain concentration of melamine is responsible for color change of AuNPs from red to purple. The surface plasmon resonance peak was shifted from 520 to 640 nm. In the presence of formaldehyde, the reaction between melamine and formaldehyde to form methylol melamine was occurred, which resulted in the decreasing of aggregation of AuNPs. Based on the anti-aggregation mechanism, formaldehyde can be detected by observing the color change of AuNPs solution containing melamine, which was monitored by UV–visible spectrophotometer. Calibration curve plotted between absorbance ratio (A640/A520) and formaldehyde concentration was made with linearity of 0 – 2000 µg L−1. The limit of detection and the limit of quantitation were found at 26.0 µg L−1 and 88.0 µg L−1, respectively. The method also provided high accuracy (%recovery in range 97.3 – 104%) and high precision (%RSD < 5.6).
Keywords: Anti-aggregation; Colorimetric sensor; Formaldehyde; Gold nanoparticles; Sea food